1971
DOI: 10.4319/lo.1971.16.2.0387
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Exchanges Between Sediments and Water in the Great Lakes‐speculations on Probable Regulatory Mechanisms1

Abstract: As long as the oxygen concentration at the sediment surface does not fall below 1 or 2 mg/liter, typical deep‐water sediments in the Great Lakes will probably be found to exert a measurable but quantitatively unimportant influence on the chemistry of the overlying waters. This conclusion is supported by the case of Windermere. The sequence of more conspicuous changes that take place when the oxygen does fall below 1 mg/liter at the interface is illustrated by the case of Esthwaite Water, representative of even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
189
1
9

Year Published

1973
1973
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(204 citation statements)
references
References 10 publications
5
189
1
9
Order By: Relevance
“…Einsele (1936) suggested that the adsorption of phosphorus on ferric oxides during an aerobic condition controlled the phosphorus flux through the sediment-water interface, while under anaerobic conditions, due to the reductive dissolution of these oxides, it could subsequently be released. Mortimer (1941Mortimer ( , 1971 demonstrated in his classical studies that the release of phosphorus was unimportant as long as the concentration of dissolved oxygen exceeded 2 mg L −1 in the overlying water. When concentration of dissolved oxygen was below 2 mg L −1 , the phosphorus previously bound by solid ferric (hydr)oxides would be released.…”
mentioning
confidence: 99%
“…Einsele (1936) suggested that the adsorption of phosphorus on ferric oxides during an aerobic condition controlled the phosphorus flux through the sediment-water interface, while under anaerobic conditions, due to the reductive dissolution of these oxides, it could subsequently be released. Mortimer (1941Mortimer ( , 1971 demonstrated in his classical studies that the release of phosphorus was unimportant as long as the concentration of dissolved oxygen exceeded 2 mg L −1 in the overlying water. When concentration of dissolved oxygen was below 2 mg L −1 , the phosphorus previously bound by solid ferric (hydr)oxides would be released.…”
mentioning
confidence: 99%
“…The homogeneous water column distributes dissolved oxygen in bottom waters, thus preventing diffusion of nutrients to bottom waters owing to oxidizing surface sediments porewater (Mortimer 1971, Conley et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In the sediment pore water, PO 4 diffuses upwards into the oxic sediment layer and can be bound to Fe-oxyhydroxides at the surface (Mortimer 1971;Krom and Berner 1981). Fe-bound P is abundant in surface sediments overlain by oxic bottom waters in the Baltic Sea (Balzer 1986;Jensen and Thamdrup 1993;Lukkari et al 2009;Mort et al 2010).…”
Section: Phosphorus Transformationsmentioning
confidence: 99%
“…In organic-rich sediments common in the Baltic Sea, O 2 consumption by mineralisation of organic matter can create reduced conditions, if the O 2 is not replenished. When Fe-oxyhydroxides are not able to form, or they form only a thin layer on the sediment surface, PO 4 is not efficiently retained (Mortimer 1971). Furthermore, in brackish and marine environments, sulphide can restrict participation of Fe in PO 4 binding by precipitating ferrosulphides (Berner 1970;Caraco et al 1989).…”
Section: Phosphorus Transformationsmentioning
confidence: 99%